Detection of Various Microplastics in Patients Undergoing Cardiac Surgery - Yang, Yunxiao; Xie, Enzehua; Du, Zhiyong; Peng, Zhan; Han, Zhongyi; Li, Linyi; Zhao, Rui; Qin, Yanwen; Xue, Mianqi; Li, Fengwang; Hua, Kun; Yang, Xiubin (Environmental science & technology, 2023)
Microplastics have been detected in human stool, lungs, and placentas, which have direct exposure to the external environment through various body cavities, including the oral/anal cavity and uterine/vaginal cavity. Crucial data on microplastic exposure in completely enclosed human organs are still lacking. Herein, we used a laser direct infrared chemical imaging system and scanning electron microscopy to investigate whether microplastics exist in the human heart and its surrounding tissues. Microplastic specimens were collected from 15 cardiac surgery patients, including 6 pericardia, 6 epicardial adipose tissues, 11 pericardial adipose tissues, 3 myocardia, 5 left atrial appendages, and 7 pairs of pre- and postoperative venous blood samples. Microplastics were not universally present in all tissue samples, but nine types were found across five types of tissue with the largest measuring 469 μm in diameter. Nine types of microplastics were also detected in pre- and postoperative blood samples with a maximum diameter of 184 μm, and the type and diameter distribution of microplastics in the blood showed alterations following the surgical procedure. Moreover, the presence of poly(methyl methacrylate) in the left atrial appendage, epicardial adipose tissue, and pericardial adipose tissue cannot be attributed to accidental exposure during surgery, providing direct evidence of microplastics in patients undergoing cardiac surgery. Further research is needed to examine the impact of surgery on microplastic introduction and the potential effects of microplastics in internal organs on human health.